THE INFLUENCE OF GREEN PRODUCT QUALITY, GREEN BRAND TRUST AND GREEN BRAND IMAGE ON GREEN PURCHASE INTENTION AND ITS IMPLICATIONS ON GREEN PURCHASE BEHAVIOR (A STUDY ON CUSTOMERS OF THE BODY SHOP PRODUCTS IN SOUTH TANGERANG CITY - Sari, Ade Ratna; Gursida, Hari; Wihartika, Doni (International Journal of Multidisciplinary Research and Literature, 2025)
A study has been conducted with the title The Influence of Green Product Quality, Green Brand Trust and Green Brand Image on Green Purchase Intention and Its Implications on Green Purchase Behavior (Study on The Body Shop Product Customers in South Tangerang City. This study aims to determine the Influence of Green Product Quality, Green Brand Trust and Green Brand Image on Green Purchase Intention and Its Implications on Green Purchase Behavior. The research sample was 370 respondents. The data collection technique used in this study was by distributing questionnaires to obtain data, with reference to the Likert scale. This study uses the Quantitative Method with Smart PLS Testing. The results of the study show that Green Product Quality has a positive and significant influence on Green Purchase Intention, Green Brand Trust has a positive and significant influence on Green Purchase Intention , Green Brand Image has a positive and significant influence on Green Purchase Intention , Green Product Quality  has a positive and significant influence on Green Purchase Behavior , Green Brand Trust has a positive and significant influence on Green Purchase Behavior, Green Brand Image has a positive and significant influence on Green Purchase Intention , Green Product Quality  has a positive and significant influence on Green Purchase Behavior positive and significant influence on Green Purchase Behaviour, Green Product Quality has a positive and significant influence on Green Purchase Behaviour through Green Purchase Intention, Green Brand Trust has a positive and significant influence on Green Purchase Behaviour through Green Purchase Intention, Green Brand Image has a positive and significant influence on Green Purchase Behaviour through Green Purchase Intention , and Green Purchase Intention has a positive and significant influence on Green Purchase Behaviour.